Disruptive innovation disclosure practices: Do board characteristics, ownership structure, and investor matter? - Indrian Supheni; Suyanto Suyanto; Tiyas Puji Utami (Universitas Muhammadiyah Yogyakarta, Indonesia, 2024)
Research aims: This study aims to analyze the effect of board characteristics, ownership structures, and investors on disruptive innovation disclosure in the annual reports of companies in Indonesia.Design/Methodology/Approach: This study used 237 cross-section data from 237 companies in the manufacturing sectors. The dependent variable in this study was obtained by analyzing the content of the company's annual report. The hypothesis in this study was then tested using multiple linear regression.Research findings: The regression test results revealed that foreign ownership affected the disclosure of disruptive innovation in manufacturing companies. Other variables, such as characteristics of the board of commissioners, members and investors, did not affect the disclosure of disruptive innovation in manufacturing companies.Theoretical contribution/Originality: Disclosure of disruptive innovation is rarely done, but this study looks at disclosure from the stakeholder theory perspective in manufacturing companies.Research limitation/Implication: This study was only limited to manufacturing companies. Meanwhile, other companies are expected to be studied in further research. In addition, more observation data can be added to strengthen the research results.